Determinantes de la rentabilidad no esperada de las empresas bancarias que cotizan en la Bolsa de Valores de Lima - Lizarzaburu, Edmundo R. (2017)
This research proposes a theoretical framework focused on explaining the unexpected or "abnormal" return of the most representative banks of the Peruvian financial system, which also have shares listed on the Lima Stock Exchange. Likewise, this paper propose a number of explanatory variables such as the ratio of allowance for loan losses (PPP), size of the bank (TAM), asset liquidity (LIQ), leverage ratio (APL), efficiency in the management (EG), fee income (ICM) and general cost ratio (RCG). Thus, an independent linear regression is performed for each bank. Finally, we found that the level of assets is the significant variable in this analysis because it serves as a barrier for new and existing competitors.